HUBUNGAN KEADAAN EKONOMI KELUARGA DI ERA PANDEMI COVID-19 DENGAN STATUS GIZI IBU HAMIL DI WILAYAH KERJA PUSKESMAS PURWOREJO KABUPATEN PURWOREJO: HUBUNGAN KEADAAN EKONOMI KELUARGA DI ERA PANDEMI COVID-19 DENGAN STATUS GIZI IBU HAMIL DI WILAYAH KERJA PUSKESMAS PURWOREJO KABUPATEN PURWOREJO - Sholichah, Nur; Zeni Rokhmah, Zeni (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2023)
ABSTRACT The impact of the Covid-19 pandemic has greatly affected the fulfillment achievement of nutritional needs of pregnant mother. Because pregnant mother who consume foods that are not nutritious, so there is a CED (Chronic Energy Deficiency) and families that hinder the Covid-19 pandemic, so that they get laid off which causes the economy to decrease. Research purposes knowing the relationship between economic conditions and the nutritional status of pregnant women in the working area of ​​the Purworejo Health Center. Reseach method analytical survey with a cross-sectional approach. Population in this study were pregnant women who visited at PMB Rosida Himawati, S.ST. The sampling technique used incidental. The setting of the result was May 2022. The data analysis test used the Chi-square. The results of the data analysis test showed that the p-value (0.006) < (0.05), then Ho was rejected and Ha was accepted so that there was a relationship between economic family conditions in the era of covid-19 pandemic and the nutritional status of pregnant women in working area of Puskesmas Purworejo, Purworejo Regency. Keywords: economic condition, nutritional status of pregnant women